Use of double-phase-sensitive detection to measure DPOAE signals - Michalski, Wojciech; Dziewiszek, Wojciech; Bochnia, Marek (Archives of Acoustics, 2007)
This paper presents a new method of measuring distortion product otoacoustic emissions (DPOAE) induced by a two-tone acoustic wave. The method is based on double-phasesensitive detection whereby it is possible to precisely measure DPOAE signals whose acoustic pressure level is even below −15 dB. Exemplary experimental results for guinea pigs are given.